The Factors Influencing Normal Childbirth Among Midwives Providing National Health Insurance Services in Tabanan Regency - Ni Putu Widiyanti; Ni Putu Widarini; I Ketut Suarjana (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2024)
Childbirth assisted by network midwives under the National Health Insurance (NHI) is expected to reduce maternal mortality in Tabanan Regency, but low utilization remains a challenge. This study aims to identify factors influencing normal childbirth at NHI network midwives in Tabanan Regency. An exploratory qualitative study was conducted in June 2024. Data were collected through in-depth interviews with 11 informants, including midwives, the Head of the Midwives Professional Organization (IBI), representatives from the District Health Office, Social Security Agency (BPJS) Health, and mothers using delivery services in midwives were selected using purposive sampling. The data were analyzed thematically. Network midwives in the NHI scheme demonstrated strengths such as positive attitudes, high motivation, and adequate skills. They also received support from professional organizations, inter-professional collaboration, and government policies, and were trusted by the community. However, challenges include a lack of information about NHI, a limited understanding of administrative procedures, low claim rates, and complex bureaucracy. The positive attitudes, motivation, and skills are strengths of network midwives, but poor knowledge of NHI procedures and low claim rates hinder service utilization. Recommended efforts include improving midwife competencies, strengthening inter-professional collaboration, utilizing social media for education, and reviewing delivery tariffs regularly.